A high scale SARS-CoV-2 profiling by its whole-genome sequencing using Oxford Nanopore Technology in Kazakhstan - Kairov, Ulykbek; Amanzhanova, Amina; Karabayev, Daniyar; Rakhimova, Saule; Aitkulova, Akbota; Samatkyzy, Diana; Kalendar, Ruslan; Kozhamkulov, Ulan; Molkenov, Askhat; Gabdulkayum, Aidana; Sarbassov, Dos; Akilzhanova, Ainur (Frontiers in Genetics, 2022)
Severe acute respiratory syndrome (SARS-CoV-2) is responsible for the worldwide pandemic, COVID-19. Whole-genome sequencing is critical for SARS-CoV-2 variant surveillance, the development of new vaccines and boosters, and the representation of epidemiological situations in the country. A significant increase in the number of COVID-19 cases confirmed in August 2021 in Kazakhstan facilitated a need to establish an effective and proficient system for further study of SARS-CoV-2 genetic variants and the development of genomic surveillance program. The SARS-CoV-2 whole-genome was sequenced according to SARS-CoV-2 ARTIC protocol (EXP-MRT001) by Oxford Nanopore Technologies at the National Laboratory Astana, Nazarbayev University, Kazakhstan to track viral variants circulating in the country. The 500 samples kindly provided by the Republican Diagnostic Center (UMC-NU) and private laboratory KDL “Olymp” were collected from individuals in Nur-Sultan city diagnosed with COVID-19 from August 2021 to May 2022 using RT-qPCR. The overall average value of sequencing depth for samples is 244X. 341 whole-genome sequences that passed quality control were deposited in GISAID database. The BA.1.1 (n=189), BA.1 (n=15), BA.2 (n=3), BA.1.15 (n=1), BA.1.17.2 (n=1) omicron lineages, AY.122 (n=119), B.1.617.2 (n=8), AY.111 (n=2), AY.126 (n=1), AY.4 (n=1) delta lineages, one sample B.1.1.7 (n=1) belongs to alpha lineage, and one sample B.1.637 (n=1) belongs to small sublineage were detected in this study. This is the first study of SARS-CoV-2 whole-genome sequencing by the ONT approach in Kazakhstan, which can be expanded for the investigation of other emerging viral or bacterial infections on the country level.